Penerapan Arsitektur Hijau pada Bangunan Shopping Mall - Perintis Jaya Laia; Sudarwani Maria; Yophie Sepdiady (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Green architecture is an approach to building design and construction that aims to reduce negative impacts on the environment while creating healthier and more efficient spaces for its users. This approach prioritizes the principle of investment by maximizing the use of resources, reducing energy consumption, managing air efficiently, and utilizing environmentally friendly materials. The goal is to create buildings that can support ecological balance, reduce carbon footprints, and provide long-term benefits for both humans and nature. The concept of green architecture plays a crucial role in addressing pollution in Jakarta, a city that is grappling with air and environmental pollution problems due to rapid urbanization. One of the key elements of green architecture is greenery, including the application of vegetation to buildings such as green roofs. These plants function to absorb pollutants, produce oxygen, and help lower the temperature of the city, thus contributing